2017
DOI: 10.1007/s00702-017-1823-7
|View full text |Cite
|
Sign up to set email alerts
|

The serotonergic system in Parkinson’s patients with dyskinesia: evidence from imaging studies

Abstract: The purpose of review is to review the current status of positron emission tomography (PET) molecular imaging of serotonergic system in Parkinson’s patients who experience levodopa-induced (LIDs) and graft-induced dyskinesias (GIDs). PET imaging studies have shown that Parkinson’s disease is characterized by progressive loss of dopaminergic and serotonergic neurons. Parkinson’s patients who experienced LIDs and GIDs have an aberrant spreading of serotonergic terminals, which lead to an increased serotonergic/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 45 publications
(85 reference statements)
0
10
0
Order By: Relevance
“…MRI studies examining cortical thickness and subcortical nuclei volume have linked both fatigue and somnolence to thalamic atrophy as well [62]. There may also be susceptibility to levodopa-induced dyskinesias [63]. This subgroup needs specific personalized strategies, including:…”
Section: Nonmotor Subtypesmentioning
confidence: 99%
“…MRI studies examining cortical thickness and subcortical nuclei volume have linked both fatigue and somnolence to thalamic atrophy as well [62]. There may also be susceptibility to levodopa-induced dyskinesias [63]. This subgroup needs specific personalized strategies, including:…”
Section: Nonmotor Subtypesmentioning
confidence: 99%
“…Network impairment in such neurodegenerative disorders has been selectively associated with neurological symptoms such as cognitive, motor, Electronic supplementary material The online version of this article (https ://doi.org/10.1007/s0041 5-020-09806 -3) contains supplementary material, which is available to authorized users. and non-motor symptoms [4][5][6][7][8]. Tools to measure impaired neurotransmitter networks integrity require either the application of PET or complex MRI methodology with contrast injection.…”
Section: Introductionmentioning
confidence: 99%
“…A study has suggested the degeneration of serotonergic terminals is an early process in the pathogenesis of PD and with preferential lower rate of degeneration as compare of dopaminergic neurons [59]. The aberrant spread of serotonergic terminals in putamen, non-physiologically converts the exogenous levodopa and results into higher swings of dopamine that develops the levodopa associated dyskinesia [60]. The cholinergic and dopaminergic neurons are highly conserved in the striatum and extensively interact bidirectionally to regulate the motor coordination, cognitive function and rewards [61].…”
Section: Discussionmentioning
confidence: 99%